Paris refashioned, 1957-1968 - Hill, Colleen 1982- (Yale University Press, 2017)
"The 1960s was one of the most exciting periods in fashion history, as shifting cultural paradigms were embraced by a generation of designers that challenged conventions and reinvented the fashion industry. This compelling volume focuses on the important but too often dismissed fashions that were created in Paris during this time. From the early couture designs of Yves Saint Laurent that initiated a trend toward a more relaxed and youthful style, to the popularity of ready-to-wear fashions by Emmanuelle Khanh - part of a new group known as the stylists - this book traces the development of Parisian fashion during the 1960s and its continuing legacy. Colleen Hill features eye-catching images from Elle and Vogue, as well as stunning examples of fashion from The Museum at FIT's world-class collection. She provides an in-depth look at the combined influences of French haute couture, ready-to-wear, and popular culture during this era. In doing so, she describes how the dominance of haute couture was challenged by the ready-to-wear movement, resulting in the rise of a vibrant, youthful, and modern aesthetic in Parisian fashion"...
Includes bibliographical references (pages 248-250)
Keywords: Geschichte 1957-1968; DESIGN / Fashion / bisacsh; DESIGN / Textile & Costume / bisacsh; ART / Collections, Catalogs, Exhibitions / Group Shows / bisacsh; Fashion design -- France -- Paris -- History -- 20th century; Fashion -- France -- Paris -- History -- 20th century; DESIGN / Fashion; DESIGN / Textile & Costume; ART / Collections, Catalogs, Exhibitions / Group Shows; Haute couture; Konfektion; Mode; Frankreich; Paris